Pre‐ and Post‐Copulatory Sexual Traits Influence Male Fitness Across a Mosaic Hybrid Zone - Logan M. Maxwell; Jennifer Walsh; Brian J. Olsen; Adrienne I. Kovach (Ecology and Evolution, 2025)
ABSTRACT Primary and secondary male sexual traits can influence the interspecific interactions of hybridizing populations, yielding fitness consequences and either promoting or restricting gene flow. In this study, we evaluated the relative male fitness of two species of hybridizing tidal marsh endemics: saltmarsh (Ammospiza caudacutus) and Nelson's sparrows (A. nelsoni) and assessed the effects of male condition and competitive ability on resulting patterns of paternity and gene flow. We compared reproductive success (number of offspring sired) among saltmarsh, Nelson's, and hybrid sparrow males (n = 125) and modeled male fitness in relation to measured pre‐copulatory (body size, fat scores, and muscle scores) and post‐copulatory (cloacal protuberance (CP) volume and sperm length) male sexual traits across two sites within the center of the hybrid zone. We found saltmarsh sparrows had higher levels of skew in fertilization success than Nelson's and greater reproductive output than both Nelson's and hybrids, suggesting interspecific competition may occur. Body size was the best predictor of reproductive success, independent of male genotypes, providing evidence for a role of pre‐copulatory sexual selection. We also found evidence of post‐copulatory sexual selection and sperm competition contributing to patterns of hybridization, with CP volume and sperm length increasing with number of offspring sired. Differential mean fitness by species may influence patterns of hybridization and has the potential to drive asymmetrical introgression; however, the drivers of male fitness differed between species and sites, suggesting the level of sexual selection and resulting patterns of gene flow are context dependent and not stable across a small sptatial scale within the center of this mosaic hybrid zone. Overall, few interspecific offspring and nearly equal backcrossing in both parental species within the center of the hybrid zone suggest mechanisms such as reinforcement exist to limit hybridization and minimize asymmetric introgression.